Complete sequence of a cDNA clone specifying sandbar shark immunoglobulin light chain: gene organization and implications for the evolution of light chains. - Hohman, V S (1992)
A full-length cDNA clone specifying sandbar shark (Carcharhinus plumbeus) immunoglobulin light chain has been isolated and sequenced. By alignment with human lambda chains, the leader, framework, complementarity-determining, joining, and constant regions are clearly identified in the shark light chain. Approximately 40-50% identity is shared between the human and shark sequences in the variable and constant regions. We have performed sequence comparisons of the individual segments and constructed phylogenetic trees for the variable region. These studies identify the shark protein as a lambda chain. In addition, the sandbar shark light chain is only distantly related to that of horned shark (Heterodontus francisci) [Shamblott, M. J. & Litman, G. W. (1989) Proc. Natl. Acad. Sci. USA 86, 4684-4688], demonstrating that the long evolutionary time of divergence among shark species has led to the generation of substantial differences in sequence. The positions of the variable, joining, and constant gene segments in 14 genomic clones have been mapped. The segments are linked in individual clusters (variable, joining, constant) occupying 3-7 kilobases. Cluster arrangement can be grouped into two patterns based upon spacing between the genes in the individual clones. This arrangement is fundamentally different from that observed in higher vertebrates.